Bacterial PCR in the diagnosis of joint infection. Issue 3 (1st March 2001) - Jalava, J; Skurnik, M; Toivanen, A; Toivanen, P; Eerola, E
Abstract : OBJECTIVES: To evaluate the value of broad range bacterial PCR in the diagnosis of joint infection and to find out if there are bacteria causing arthritis which are not cultivable by the present methods. METHODS: Polymerase chain reaction (PCR) with broad range bacterial primers and DNA sequencing (bacterial PCR) was used to analyse 154 synovial fluid (SF) samples from patients with different arthritic diseases. RESULTS: Bacterial DNA was detected in 18 SF samples, including samples from six patients with culture proven purulent arthritis, and from three patients with possible purulent arthritis. Three samples from patients with culture confirmed purulent arthritis remained negative in bacterial PCR. CONCLUSIONS: The results indicate that in the usual diagnostic laboratory setting bacterial PCR does not offer any obvious advantage over bacterial culture in the microbiological diagnosis of joint infection.